Collaborative syllabus design for studying information work. Issue 1 (24th October 2017) - Buchanan, Sarah A.; Bullard, Julia; Aspray, William; Bailey, Diane; Barker, Lecia; Carter, Daniel; Clement, Tanya; Gottschlich, Nicholas; Howison, James; McLaughlin, Stephen; Ocepek, Melissa; Sholler, Daniel; et al.
ABSTRACT: Recognizing that current curricula address but a sliver of the wide range of careers pursued by information studies graduates, a team worked collaboratively to design a syllabus for a graduate course dedicated to exploring the societal frames and characteristics of information work. Ultimately comprising 10 modules, the syllabus centers students' awareness of an expanded occupational landscape and evaluation of policies and labor structures impacting information workers. Created over the course of a semester, the syllabus complements an earlier set of empirical studies that revealed areas in which information educators might focus future teaching efforts. This paper articulates the role for iterative and collaborative processes in curriculum development and doctoral study around information work – a research arena requiring macroscopic and future‐oriented thinking. We present the topical and pedagogical organization of the new syllabus and suggest paths forward for integrating its key concepts at other graduate and undergraduate levels of information studies coursework.